Relativistic Kinematics

Relativistic kinematics refers to the study of motion and interactions of objects that are moving at speeds comparable to the speed of light, as described by Albert Einstein's theory of special relativity. classNameical or Newtonian mechanics is a special case of kinematics that works well for objects moving at speeds much less than the speed of light. However, as an object's speed approaches the speed of light (denoted by c), classNameical mechanics fails to accurately describe its behavior.

Relativistic kinematics introduces corrections to classNameical kinematics when dealing with high speeds. Some key features of relativistic kinematics include:

  1. Time Dilation: Time is relative, and it passes at different rates for observers in different reference frames. As an object approaches the speed of light, time for that object appears to pass more slowly for an observer at rest.

  2. Length Contraction: Lengths of objects in motion appear shorter in the direction of motion as observed by an observer at rest.

  3. Relativistic Momentum and Energy: classNameical concepts of momentum and kinetic energy are modified to incorporate relativistic effects. The total energy of an object includes not just its rest mass energy but also its kinetic energy due to motion.

  4. Invariant Mass: While the relativistic mass of an object increases with its speed, the rest mass (or invariant mass) remains constant. The invariant mass is a fundamental property of the object and is the same in all reference frames.

  5. Lorentz Transformations: These are mathematical equations that describe how space and time coordinates transform between different inertial frames in special relativity.

Velocity Addition Theorem

Derivation

Let us consider two frames SS and SS', frame SS' is moving with constant velocity vv relative to frame SS along the positive direction of the X-axis.

Let us express the velocity of the body in these frames. Suppose that body moves a distance dxdx in time dtdt in frame SS and through a distance dxdx' in the time dtdt' in the system SS' from point PP to QQ. Then

Lorentz Transformation Figure

dxdt=udxdt=u    —— equation 1\frac{dx}{dt} = u\qquad \frac{dx'}{dt'}= u' \; \; \text{------ equation 1}

From Lorentz's inverse transformation

x=K(x+vt)    —— equation 2x=K\left ( x'+vt' \right )\; \; \text{------ equation 2}

t=K(t+vxc2)    —— equation 3t=K '\left ( t'+\frac{v\cdot x'}{c^{2}} \right )\; \; \text{------ equation 3}

Differentiate the equation2equation - 2 and equation3equation - 3 with respect to tt'

dxdt=K(dxdt+v)    —— equation 4\frac{dx}{dt'}= K \left ( \frac{dx'}{dt'}+v \right )\; \; \text{------ equation 4}

dtdt=K(1+vc2dxdt)    —— equation 5\frac{dt}{dt'}= K ' \left ({1}+\frac{v}{c^{2}} \cdot \frac{dx'}{dt'} \right )\; \; \text{------ equation 5}

Now divide the equation4equation - 4 by equation5equation - 5. So

dxdtdtdt=(dxdt+v1+vc2dxdt)\frac{\frac{dx}{dt'}}{\frac{dt}{dt'}} = \left ( \frac{\frac{dx'}{dt}+v}{1+\frac{v}{c^{2}}\cdot \frac{dx'}{dt'} } \right ) \qquad

From Lorentz Transformation K=KK =K '. So above equation can be written as:

dxdt=u+v1+uvc2\frac{dx}{dt} = \frac{u' +v}{1+ \frac{u'v}{c^{2}}}

From equation1equation - 1. The above equation can be written as:

u=u+v1+uvc2u = \frac{u' +v}{1+ \frac{u'v}{c^{2}}}

This equation represents the relativistic law of addition of velocities with respect to an observer at frame-SS whereas in classNameical mechanics it is simply u=u+vu = u'+v. There is the following point observed from the addition of the velocities equation.

  • When u=cu' = c, Then u=c+v1+vcu =\frac{c+v}{1+\frac{v}{c}} So, on solving we get

    u=cu=c

  • When v=cv = c, Then u=u+c1+ucc2u =\frac{u'+c}{1+\frac{u'c}{c^{2}}} So, on solving we get

    u=cu=c

  • When u=cu' = c and v=cv = c, Then u=c+c1+c2c2u =\frac{c+c}{1+\frac{c^2}{c^{2}}} So, on solving we get

    u=cu=c

    This shows that the addition of the velocity of light simply reproduces the velocity of light. It means that the velocity of light in a vacuum is the maximum achievable velocity in nature and no signal and any object can travel faster than the velocity of light in a vacuum.

Numericals

Variation of Mass with Velocity

Derivation

Let there are two inertial frames of references SS and SS'. SS is the stationary frame of reference and SS' is the moving frame of reference. At time t=t=0t=t'=0 that is in the start, they are at the same position that is Observers OO and OO' coincides. After that SS frame starts moving with a uniform velocity vv along x axis.

Variation of mass with velocity Figure

Suppose there are two particles moving in opposite direction in frame SS'. Velocity of particle A will be uu and of B will be u-u' according to the observer OO'.

Let us study the velocities and mass of these particles from frame SS. Velocity of A is u1u_1 and B is u2u_2 from frame SS and these are given by velocity addition theorem:

u1=u+v1+uvc2u_1 = \frac{u' + v}{1 + \frac{u'v}{c^2}}     and    \; \; and \; \; u2=u+v1uvc2u_2 = \frac{-u' + v}{1 - \frac{u'v}{c^2}}     —— equation 1 and 2\; \; \text{------ equation 1 and 2}

Let m1m_1 and m2m_2 are the mass of A and B from frame SS respectively. As the particles are moving to each other, at certain instant they will collide and momentarily came to rest. But even when they came to rest, they travel with the velocity of the frame SS' that is with vv.

According to the law of conservation of momentum:

Momentum before collision = Momentum after collision

Thus, m1u1+m2u2=m1v+m2v=(m1+m2)v    m_1u_1 + m_2u_2 = m_1v + m_2v = (m_1 + m_2)v \; \;

—— equation 3\text{------ equation 3}

From equation1  and  2equation - 1\; and\; 2, putting values of u1u_1 and u2u_2 in equation3equation - 3, We get:-

m1u+v(1+uvc2)+m2u+v(1uvc2)=(m1+m2)vm_1 \frac{u' + v}{\left(1 + \frac{u'v}{c^2}\right)} + m_2 \frac{-u' + v}{\left(1 - \frac{u'v}{c^2}\right)} = (m_1 + m_2)v

m1[u+v1+uvc2v]=m2[vu+v1uvc2]m_1\left[\frac{u' + v}{1 + \frac{u'v}{c^2}} - v\right] = m_2\left[v - \frac{-u' + v}{1 - \frac{u'v}{c^2}}\right]

Then take LCM of terms in the bracket and solve, we get

m1(11+uvc2)=m2(11uvc2)m_1\left(\frac{1}{1 + \frac{u'v}{c^2}}\right) = m_2\left(\frac{1}{1 - \frac{u'v}{c^2}}\right)

oror

m1m2=1+uvc21uvc2    —— equation 4\frac{m_1}{m_2} = \frac{1 + \frac{u'v}{c^2}}{1 - \frac{u'v}{c^2}}\; \; \text{------ equation 4}

Now square equation1equation - 1, then divide both sides by c2c^2 and subtract both sides by 1, we get

1u12c2=11c2(u+v(1+uvc2))21 - \frac{u_1^2}{c^2} = 1 - \frac{1}{c^2}\left(\frac{u' + v}{(1 + \frac{u'v}{c^2})}\right)^2

By taking LCM on RHS and solving, we get

1u12c2=1+u2v2c4u2c2v2c2(1+uvc2)2    —— equation 51 - \frac{u_1^2}{c^2} = \frac{1 + \frac{u'^2v^2}{c^4} - \frac{u'^2}{c^2} - \frac{v^2}{c^2}}{(1 + \frac{u'v}{c^2})^2} \; \; \text{------ equation 5}

Similarly by squaring equation2equation - 2, then dividing both sides by c2c^2 and subtracting both sides by 1, we get

1u22c2=1+u2v2c4u2c2v2c2(1uvc2)2    —— equation 61 - \frac{u_2^2}{c^2} = \frac{1 + \frac{u'^2v^2}{c^4} - \frac{u'^2}{c^2} - \frac{v^2}{c^2}}{(1 - \frac{u'v}{c^2})^2}\; \; \text{------ equation 6}

On dividing equation6    by    5equation - 6\; \; by\; \; 5, we get

(1u22c2)(1u12c2)=(1+uvc2)2(1uvc2)2\frac{(1 - \frac{u_2^2}{c^2})}{(1 - \frac{u_1^2}{c^2})} = \frac{(1 + \frac{u'v}{c^2})^2}{(1 - \frac{u'v}{c^2})^2}

Take square root on both sides

1u22c21u12c2=1+uvc21uvc2    —— equation 7\frac{\sqrt{1 - \frac{u_2^2}{c^2}}}{\sqrt{1 - \frac{u_1^2}{c^2}}} = \frac{1 + \frac{u'v}{c^2}}{1 - \frac{u'v}{c^2}} \; \; \text{------ equation 7}

Now compare equations4    and    7equations - 4\; \; and\; \; 7, we get

m1m2=1u22c21u12c2    —— equation 8\frac{m_1}{m_2} = \frac{\sqrt{1 - \frac{u_2^2}{c^2}}}{\sqrt{1 - \frac{u_1^2}{c^2}}}\; \; \text{------ equation 8}

This is more of a complicated result. To make this result simple, let us assume that the particle B is in the state of rest from frame SS that is it has zero velocity before collision

Thus, u2=0u_2 = 0     and    \; \; and \; \; m2=m0m_2 = m_0

Where m0m_0 is the rest mass of the particle, Therefore equation7equation - 7 becomes

m1m0=11u12c2\frac{m_1}{m_0} = \frac{1}{\sqrt{1 - \frac{u_1^2}{c^2}}}

Also assume u1=v    and    m1=mu_1 = v \; \; and \; \; m_1 = m, Therefore above equation becomes

mm0=11v2c2\frac{m}{m_0} = \frac{1}{\sqrt{1 - \frac{v^2}{c^2}}}

oror

m=m01v2c2m = \frac{m_0}{\sqrt{1 - \frac{v^2}{c^2}}}

This equation represents the equation of the variation of mass with the velocity. It shows that if a particle or anything moves with a speed comparable to the speed of the light then its mass will appeared increased.

Mass-Energy Equivalence

Topic asked in Applied Physics 2023 (CBCS/NEP) question paper Section A - 2(a).

In classNameical mechanics, the mass of a moving particle is independent of its velocity. Contrary to this aspect, by Einstein’s special theory of relativity, the mass of a moving body depends upon its velocity and is given by

m=m01v2/c2(i) m = \frac{m_0}{\sqrt{1-v^2/c^2}} \quad \text{(i)}

where vv is the velocity of the body, m0m_0 is its rest mass and cc is the velocity of light. The increase in energy of the particle by the applications of force may be defined in terms of work done which is the product of the force and the displacement. According to Newton’s second law of motion, the rate of change of momentum of the particle is equal to the force applied on it. Thus

F=d(mv)dt(ii) F = \frac{d(mv)}{dt} \quad \text{(ii)}

If the particle is displaced a distance dxdx by the application of force FF, the work done FdxFdx is stored as kinetic energy EKE_K in the body. Then

dW=dEK=Fdx(iii) dW = dE_K = Fdx \quad \text{(iii)}

By using Eqs. (ii) and (iii), we get

dEK=d(mv)dtdx dE_K = \frac{d(mv)}{dt} dx

or

dEK=dxdtd(mv)(iv) dE_K = \frac{dx}{dt} d(mv) \quad \text{(iv)}

or

dEK=v[dm+mdν] dE_K = v [dm + m d\nu] =v2dm+mvdν(v) = v^2 dm + m v d\nu \quad \text{(v)}

But

m=m01v2c2 m = \frac{m_0}{\sqrt{1 - \frac{v^2}{c^2}}}

or

m2=m02c2c2v2 m^2 = \frac{m_0^2 c^2}{c^2 - v^2}

or

m2c2m2v2=m02c2(vi) m^2 c^2 - m^2 v^2 = m_0^2 c^2 \quad \text{(vi)}

By differentiating Eq. (vi), we have

2mdmc22mdvv22vdmv=0 2m dm c^2 - 2m dv v^2 - 2v dm v = 0

or

dmc2=v2dm+mvdv(vii) dm c^2 = v^2 dm + m v dv \quad \text{(vii)}

By using Eqs. (v) and (vii), we get

dEK=dmc2(viii) dE_K = dm c^2 \quad \text{(viii)}

Thus, from Eq. (viii) it is clear that the change in kinetic energy is directly proportional to the change in mass. If the body is at rest, its velocity will be zero and hence the change in kinetic energy will be zero. Therefore, its mass will be m0m_0. If the body moves with velocity vv, then its mass becomes mm and its kinetic energy becomes EKE_K. Therefore, by integrating equation (viii), we get

0EKdEK=c2m0mdm \int_0^{E_K} dE_K = c^2 \int_{m_0}^m dm

or

EK=c2[mm0]=mc2m0c2 E_K = c^2 [m - m_0] = mc^2 - m_0 c^2

or

E=mc2=EK+m0c2(ix) E = mc^2 = E_K + m_0 c^2 \quad \text{(ix)}

From Eq. (ix), it is clear that E=mc2E = mc^2 is the total energy. It is the sum of kinetic and rest mass energy. That is,

E=mc2 E = mc^2

This relation is called Einstein’s mass energy relation.

Evidence For E=mc2E = mc^2

  1. Nuclear Reactions: In nuclear fission and fusion reactions, the total mass of the products is slightly less than the total mass of the reactants. This "missing" mass has been converted into energy, which is released in the reaction. For example, in the fusion reactions that power the sun, hydrogen nuclei fuse to form helium, releasing energy in accordance with E=mc2E = mc^2.

  2. Particle-Antiparticle Annihilation: When a particle meets its antiparticle, they annihilate each other, converting their total mass into energy, typically in the form of photons. For instance, when an electron and a positron annihilate, they produce gamma rays with an energy equivalent to the combined mass of the electron and positron.

  3. Energy Production in Nuclear Power Plants: Nuclear power plants harness the energy released from fission reactions of heavy nuclei like uranium-235. The mass defect (difference in mass before and after the reaction) is converted into energy, demonstrating the principle of E=mc2E = mc^2.

  4. Experimental Measurements: Precise measurements of the masses of nuclei before and after reactions, and the energy released, confirm the mass-energy equivalence. Experiments with particle accelerators also validate the relationship, as the energy of particles moving close to the speed of light agrees with predictions from E=mc2E = mc^2.

Einstein Relation Between Energy And Momentum

How's article quality?

Last updated on -

Page Contents